ผลของวิธีการหุงต่อปริมาณกรดแกมมาอะมิโนบิวทิริก (กาบา) และสมบัติทางเคมีกายภาพของข้าวกล้องงอก - สรรพวรสถิตย์, อินทาวุธ; ปานวรณ์, กรุณาพร; เกียรติเรืองไกร, ชุติกา; ชัยวานิชศิริ, สายวรุฬ (Journal of Food Technology, Siam University, 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาผลของวิธีการหุงต่อปริมาณกรดแกมมาอะมิโนบิวทิริก (กาบา) และสมบัติทางเคมีกายภาพของข้าวกล้องงอกพันธุ์ชัยนาท 1 โดยเตรียมข้าวกล้องงอกหุงสุก 5 วิธี คือหุงด้วยหม้อหุงข้าวไฟฟ้าแบบมีการซาว และไม่มีการซาว หุงด้วยไมโครเวฟ หุงแบบเช็ดน้า และแบบไม่เช็ดน้ำ พบว่าวิธีการหุงมีผลต่อปริมาณกาบาอย่างมีนัยสาคัญ (p≤0.05) โดยข้าวกล้องงอกหุงสุกที่ผ่านการหุงด้วยหม้อหุงข้าวไฟฟ้าแบบไม่มีการซาว มีปริมาณกาบาสูงกว่าการหุงด้วยวิธีอื่นๆ ในขณะที่การหุงด้วยหม้อหุงข้าวแบบเช็ดน้ำมีปริมาณกาบาต่ำที่สุด เมื่อศึกษาคุณภาพการหุง พบว่าอัตราส่วนการขยายตัว และอัตราส่วนการยืดตัวของเมล็ดข้าวที่ผ่านการหุงทั้ง 5 วิธี ไม่มีความแตกต่างอย่างมีนัยสาคัญ (p>0.05) ข้าวกล้องงอกที่มีอัตราการดูดซับน้ำสูงสุด ได้แก่ข้าวกล้องงอกที่ผ่านการหุงด้วย หม้อหุงข้าวไฟฟ้าแบบมีการซาว ไม่มีการซาว และหุงแบบไม่เช็ดน้ำ เมื่อวิเคราะห์คุณสมบัติทางเคมีกายภาพของข้าวกล้องงอกที่ผ่านการหุงสุกทั้ง 5 วิธี พบว่าไม่มีความแตกต่างของสี ( E) (p>0.05) สาหรับค่าความแข็ง ข้าวกล้องงอกที่ผ่านการหุงด้วยไมโครเวฟมีค่าสูงที่สุด (p≤0.05) และยังพบว่าระดับการเกิดเจลาติไนซ์ของข้าวกล้องงอกหุงสุกแต่ละวิธีอยู่ในช่วงร้อยละ 62.14–68.36 Effect of Cooking Methods on -aminobutyric Acid Content and Physico-chemical Properties of Germinated Brown Rice The objective of this research was to determine effect of cooking methods on -aminobutyric acid (GABA) content and physico-chemical properties of cooked germinated brown rice (GBR). The GABA content in cooked GBR prepared by five different cooking methods including electric cooker (with and without washing rice before cooking), microwave oven, and two conventional cooking methods (with and without discarding excess water after rice was cooked). The results showed that cooking methods significantly affected GABA contents (p≤0.05). The GABA content of cooked GBR by electric cooker method (without washing rice before cooking) was the highest one, while conventional method (with discarding excess water after rice was cooked) was the lowest one. For cooking quality, expansion and elongation ratio of all cooked GBR were not significantly different (p>0.05). In addition, water uptake ratio of cooked GBR prepared by electric cooker and conventional methods without discarding excess water after rice was cooked were the highest. No significant color difference ( E) was found in each cooked GBR (p>0.05), while the hardness of GBR cooked by microwave was the highest (p≤0.05). It was also found that the degree of gelatinization of all cooked GBR were between 62.14–68.36%.